Report of an evaluation meeting - Lolas Stepke, Fernando; Rodríguez Yunta, Eduardo (Acta Bioethica, 2011)
Ethics of biomedical and psychosocial research program, Interdisciplinary Center for Studies on Bioethics, University of Chile, Grant Fogarty International Center R25TWOO6056